Mechanical Signaling in the Pathophysiology of Critical Illness Myopathy - Kalamgi, Rebeca C.; Larsson, Lars (Frontiers in Physiology, 2016)
The complete loss of mechanical stimuli of skeletal muscles, i.e., the loss of external strain, related to weight bearing, and internal strain, related to the contraction of muscle cells, is uniquely observed in pharmacologically paralyzed or deeply sedated mechanically ventilated intensive care unit (ICU) patients. The preferential loss of myosin and myosin associated proteins in limb and trunk muscles is a significant characteristic of critical illness myopathy (CIM) which separates CIM from other types of acquired muscle weaknesses in ICU patients. Mechanical silencing is an important factor triggering CIM. Microgravity or ground based microgravity models form the basis of research on the effect of muscle unloading-reloading, but the mechanisms and effects may differ from the ICU conditions. In order to understand how mechanical tension regulates muscle mass, it is critical to know how muscles sense mechanical information and convert stimulus to intracellular biochemical actions and changes in gene expression, a process called cellular mechanotransduction. In adult skeletal muscles and muscle fibers, this process may differ, the same stimulus can cause divergent response and the same fiber type may undergo opposite changes in different muscles. Skeletal muscle contains multiple types of mechano-sensors and numerous structures that can be affected differently and hence respond differently in distinct muscles